Examining Subject-Specific Information Literacy Elements on Economics and Business Administration for Use in a MOOC - Dreisiebner, Stefan (Information Literacy in Everyday Life, 2019)
Recent literature on developing Information Literacy (IL) of students suggests that curricula should not only involve generic skills, but also knowledge about subject-specific content and research practices. While there are already several studies examining subject-specific IL in various contexts, no thorough analysis has been performed so far to identify the main resources that are addressed in various IL teaching materials for economics and business administration. Therefore, this paper presents a qualitative content analysis of several subject-specific teaching materials on IL for economics and business administration, available either as books or as publicly accessible online resources. The results reveal a strong focus of subject-specific IL teaching materials for economics and business administration on fact databases. In an additional step, the results of the analysis are used to suggest the content of a subject-specific extension on economics and business administration for a generic MOOC (Massive Open Online Course).